(untitled) (Economic and Political Thought, 2023)
The purpose of this article is to provide a framework for reflection, by descri- bing the role of quality management on organisational learning in Moroccan certified SMEs. After presenting a theoretical revue related to our main question, we will show the results of an exploratory study based on three different qualitative study methods (documentary study, semi-directive inte- rviews and non-participating observation) conducted on an agro-food SME. This analysis was carried out in two stages: first, by studying the specificity of the deployment of quality management in this SME, and then by examining the place of quality management in the dynamics of organisational learning and knowledge development.